Sukarno Muda : biografi pemikiran 1926-1933 - Kasenda, Peter (Indonesia : Komunitas Bambu, 2010)
On political thoughts of Soekarno, the first president of the Republic of Indonesia.
Includes bibliographical references (p. 139-145) and index.
Keywords: Soekarno, -- 1901-1970 -- Political and social views; Presidents -- Indonesia; Indonesia -- Politics and government -- 1950-1966.